Impact of Hanseniaspora Vineae in Alcoholic Fermentation and Ageing on Lees of High-Quality White Wine - Juan Manuel Del Fresno; Carlos Escott; Iris Loira; José Enrique Herbert-Pucheta; Rémi Schneider; Francisco Carrau; Rafael Cuerda; Antonio Morata (Fermentation, 2020)
Hanseniaspora vineae is an apiculate yeast that plays a significant role at the beginning of fermentation, and it has been studied for its application in the improvement of the aromatic profile of commercial wines. This work evaluates the use of H. vineae in alcoholic fermentation compared to Saccharomyces cerevisiae and in ageing on the lees process (AOL) compared to Saccharomyces and non-Saccharomyces yeasts. The results indicated that there were not significant differences in basic oenological parameters. H. vineae completed the fermentation until 11.9% v/v of ethanol and with a residual sugars content of less than 2 g/L. Different aroma profiles were obtained in the wines, with esters concentration around 90 mg/L in H. vineae wines. Regarding the AOL assay, the hydroalcoholic solutions aged with H. vineae lees showed significantly higher absorbance values at 260 (nucleic acids) and 280 nm (proteins) compared to the other strains. However, non-significant differences were found in the polysaccharide content at the end of the ageing process were found compared to the other yeast species, with the exception of Schizosaccharomyces pombe that released around 23.5 mg/L of polysaccharides in hydroalcoholic solution. The use of H. vineae by the wineries may be a viable method in fermentation and AOL to improve the quality of white wines.